Evaluation of a central giant cell granuloma and a sialolithiasiswith cone beam computed tomography and ultrasonography: a case report - BORAHAN, MEHMET OĞUZ; BAYRAM, FERİT; ERÇALIK YALÇINKAYA, ŞEBNEM (My University, 2022)
Central giant cell granuloma (CGCG) is a benign intraosseous tumor that can cause rapid enlargement, expansion and/or perforation of cortical bone and has no significant etiology. Its differential diagnosis depends on both histological and systemic examination combined with the radiologic findings. In this case report, a CGCG case located in the anterior maxilla revealing a fibromatous and erythematous painless swelling of a 72 – year old female patient with a sialolithiasis as an incidental finding was aimed to be presented by orthopantomagram (OPG), periapical,

Santral dev hücreli granuloma (SDHG) etyolojisi belirgin olmayan benign bir intraosseöz tümör olup hızlı büyümeye, ekspansiyona ve/veya kortikal kemikte perforasyona neden olabilir. Ayırıcı tanıları histolojik ve sistemik bulgulara da bağlı olup, radyolojik bulgular ile beraber değerlendirilmelidir. Bu olgu sunumunda 72 yaşındaki kadın hastanın maksilla anterior bölgesinde bulunan, fibromatöz ve eritematöz bir şişliğe neden olan ağrısız bir SDHG olgusu sunulacaktır. Ayrıca, tesadüfi bulgu olarak sialolith ile karşılaşılmıştır. SDHG ve siyalolit; ortopantomagram (OPG), periapikal radyografi, Konik Işınlı Bilgisayarlı Tomografi ve ultrasonografi ile değerlendirilmiştir.
Keywords: santral dev hücreli granülom; siyalolit; ultrasonografi; konik ışınlı bilgisayarlı tomografi; central giant cell granuloma; sialolithiasis; ultasonography; cone beam computer tomography; central giant cell granuloma; sialolithiasis; ultasonography; cone beam computer tomography; santral dev hücreli granülom; siyalolit; ultrasonografi; konik ışınlı bilgisayarlı tomografi